Oil Quantity, Chemical and Organoleptic Properties of Three Olive Cultivars Grown under Irrigation at a Typical Arid Region in Jordan as Influenced by Harvesting Method and Date - Alfrriyeh, Hala; Al-Absi, Khalid; Ayoub, Salam (Jordan Journal of Agricultural Sciences, 2022)
An experiment was conducted to investigate the influence of harvesting method and harvesting date on the quality and quantity of three olive genotypes. Olive fruits of cultivars "Ayvalik", "Grossa de Spain" and "Nabali" were harvested on October 20 and November 13, 2017, using hand and mechanical (by combs) harvesting methods. Olive fruits were pressed then, olive oil samples were analyzed for acidity, peroxide value, refractive index, olive oil percentage, and sensory properties. The results showed that the harvesting method did not significantly affect oil quantity and chemical analysis, but affected sensory properties of olive oil, where the harvesting method by hand gave the highest (fruity, bitter, and pungent) and the lowest negative attributes (fusty, musty and rancid). Furthermore, as ripening progressed, there was an increase in olive oil percentage, oil acidity and peroxide value. The positive attributes (fruity, bitter and pungent) were significantly decreased while negative attributes (fusty, musty and rancid) were increased as ripening progressed. On the contrary, the refractive index (at 25°C) remains almost constant. The response of olive cultivars to harvesting was inconstant and did not respond similarly, "Ayvalik" had the highest acidity and peroxide value, while "Grossa de Spain" had the highest oil percentage. In addition, "Nabali" had the highest positive attributes. The lowest acidity, peroxide value and negative attributes were obtained for "Nabali". The result proved that olive cultivars and harvesting date and method combine together to influence acidity, peroxide value and sensory properties (fusty, musty, rancid, fruity, and bitter) of olive oil.